Techtome explores: bridging knowledge gaps and fostering digital literacy / Muhammad Harraz Muqri, Nur Maisarah Syasya and Abdul Ismail Mohd Jawi - Azhar, Muhammad Harraz Muqri; Arisfadillah, Nur Maisyarah Syasya; Mohd Jawi, Abdul Ismail (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The Techtome Explorers program, organized by the final-year students of class IM110 5C pursuing a Diploma in Information Management, unfolded as a one-day initiative to provide exposure and insights into science management. The program involved one project advisor and 21 students who diligently worked to enhance information skills, promote digital literacy, and underscore the evolving significance of libraries in the digital era. On January 7, 2024, at Pusat Jagaan Nur Murni in Sarawak, the Techtome Explorers program brought together final-year students from the IM110 5C Diploma in Information Management group and participants from the care center. This initiative was meticulously aligned with the requirements of the IMD314 course, aiming to extend information access, facilitate knowledge sharing, and enhance information management skills within the local community. The program targeted 38 participants at Pusat Jagaan Nur Murni, aged 4–12 years—the project team, led by Project Advisor Ts. Abdul Ismail Bin Mohamad Jawi, included project leader Nur Aisyah Umayrah Binti Ahmad Jaffary, leader assistant Nabilah Athirah Binti Abdul Rani, secretary Nur Maisarah Syasya Binti Arisfadillah, and treasurer Muhammad Harraz Muqri Bin Azhar.